Effect of elevated temperature on mechanical properties of normal strength concrete: An overview - Tanash, Alaa Omar; B. H., Abu Bakar; Khairunisa, Muthusamy; AL Biajawi, Mohammad I. (Elsevier Ltd, 2023)
Concrete is frequently used in construction owing to its advantageous mechanical characteristics, including its high compressive strength, durability, workability, and fire resistance. Nevertheless, sustained exposure to fire can result in these qualities deteriorating, which poses a serious risk to concrete buildings. As a result, it is critical that researchers investigate how exposure to fire affects the mechanical characteristics of concrete in order to address this problem. Temperature, environmental conditions, the composition of the concrete mixture, and other factors all have an impact on the thermal and mechanical characteristics of concrete. This work seeks to give an overview of how exposure to fire affects the mechanical characteristics of concrete and to highlight areas that require further research. According to the study, there are three main stages that normal concrete strength goes through. The first stage sees a slight increase in strength between 20 and 300°Celsius, followed by a sharp decrease between 300 and 800°Celsius, and finally a complete loss of strength above 800°. Moreover, the fire response of concrete is strongly influenced by factors including the kind of aggregate, moisture content, concrete grade, additives, heating rate, and heating time. By making optimal use of admixtures, the fire behavior can be significantly improved.